2012
DOI: 10.1073/pnas.1207977109
|View full text |Cite
|
Sign up to set email alerts
|

Structure and molecular mechanism of an anion-selective mechanosensitive channel of small conductance

Abstract: Mechanosensitive (MS) channels are universal cellular membrane pores. Bacterial MS channels, as typified by MS channel of small conductance (MscS) from Escherichia coli (EcMscS), release osmolytes under hypoosmotic conditions. MS channels are known to be ion selective to different extents, but the underlying mechanism remains poorly understood. Here we identify an anion-selective MscS channel from Thermoanaerobacter tengcongensis (TtMscS). The structure of TtMscS closely resembles that of EcMscS, but it lacks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 37 publications
(60 reference statements)
3
91
0
Order By: Relevance
“…The cytoplasmic domain is also considered to have a role in the adaptation and inactivation of the channel 25,26,29 and has been suggested to serve as a sensor for cytoplasmic crowding 19,30 . Furthermore, it has been proposed that the MscS cytoplasmic vestibulum may have the role of an ion-selectivity filter in this channel 6,20,31,32 .…”
mentioning
confidence: 99%
“…The cytoplasmic domain is also considered to have a role in the adaptation and inactivation of the channel 25,26,29 and has been suggested to serve as a sensor for cytoplasmic crowding 19,30 . Furthermore, it has been proposed that the MscS cytoplasmic vestibulum may have the role of an ion-selectivity filter in this channel 6,20,31,32 .…”
mentioning
confidence: 99%
“…Unlike MscL, which has no preference for any ions, MscS exhibits a weak preference for anions compared with cations (43,95,140). This weak ion selectivity has recently been shown to originate from the charged residues within seven vestibular portals in the MscS cytoplasmic chamber, which is interesting, because, unlike voltage-gated K + , Na + and Ca 2 + channels, the selectivity of MscS is not determined by charged residues in the channel pore but by residues outside the pore in the waterfilled cytoplasmic domain (36,47,170).…”
Section: Structure Of Mscsmentioning
confidence: 96%
“…1). 19 Analysis of EcMscS/TtMscS chimeras provides evidence that the difference in ion selectivities can be attributed in part, to this β-barrel sequence (which is distinct from the middle β-domain, indicated in blue). Elaborations to this C-terminal β-barrel sequence may in fact underlie the ability to transport specialized solutes such as glutamate.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…We previously demonstrated that EcMscS can be expressed mechanosensitive channel pore through the binding of ions, small molecules or other proteins. 11,14 Several MscS homologs have been characterized by single-channel electrophysiology including MscMJ and MscMJLR from Methanococcus jannaschii, 15 MscK and MscM from E. coli, [16][17][18] TtMscS from Thermoanaerobacter tengcongensis, 19 MscCG from Corynebacterium glutamicum 20 and MSC1, a chloroplasttargeted homolog from the green alga Chlamydomonas reinhardtii. 21 In addition, a family of bacterial cyclic nucleotide gated channels with homology to MscS has been reported.…”
Section: Electrophysiological Characterization Ofmentioning
confidence: 99%
See 1 more Smart Citation